2003
DOI: 10.4269/ajtmh.2003.69.6_suppl.0690005
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Properties of Dengue Viruses Following Serial Passage in Primary Dog Kidney Cells: Studies at the University of Hawaii

Abstract: Abstract. Serial passage at low dilution of seven different wild-type dengue (DEN) viruses into primary dog kidney (PDK) cell cultures placed selective pressure that resulted in the following changes from parental phenotype: smaller plaques in LLC-MK2 cells, absent plaque formation in green monkey kidney cells, lack of a cytopathic effect in LLC-MK2 cells, shut-off of virus replication at high temperatures (temperature sensitivity), reduced virulence for rhesus monkeys manifested by reduced or absent viremia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…In contrast the 16007/ V virus, which also plaques well in Vero cells had a better infectivity profile for rhesus monkeys causing viremia almost 10-fold higher with much longer duration. Viremia and seroconversion in all recipient animals after inoculation of rhesus monkeys with DENV-1 16007 has been reported (Halstead et al 1973a, Halstead & Marchette 2003. Halstead et al (1973a) observed that most rhesus monkeys receiving the 16007 virus had viremias for 5-6 days a result which is similar to ours.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In contrast the 16007/ V virus, which also plaques well in Vero cells had a better infectivity profile for rhesus monkeys causing viremia almost 10-fold higher with much longer duration. Viremia and seroconversion in all recipient animals after inoculation of rhesus monkeys with DENV-1 16007 has been reported (Halstead et al 1973a, Halstead & Marchette 2003. Halstead et al (1973a) observed that most rhesus monkeys receiving the 16007 virus had viremias for 5-6 days a result which is similar to ours.…”
Section: Discussionsupporting
confidence: 82%
“…It belongs to genotype II (Southeast Asia/South Pacific; Rico-Hesse 2003). The virus was propagated by serial passages in BSC-1 (3 times) cells, in LLC-MK 2 (4 times) and two more in T. amboinensis mosquitoes (Halstead & Marchette 2003). It was further passaged in C6/36 cells another 5 times.…”
Section: Denv-3 H87mentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that the MID 50 4 FFU for its derived attenuated vaccine (18,35). Conceivably, the infectivity of DENVs depends on the serotype and passage history.…”
Section: Discussionmentioning
confidence: 88%